Treatment Options for Patients with Type 2 Diabetes Mellitus during the Fasting Month of Ramadan - Loh, Huai Heng; Kamaruddin, Nor Azmi (Annals, Academy of Medicine, Singapore, 2020)
During Ramadan, Muslims fast from sunrise (Sahur) to sunset (Iftar) and are required to abstain from food and fluids, including oral and injectable medications. Patients with diabetes who fast during Ramadan are at risk of developing hyperglycemia with increased risk of ketoacidosis, hypoglycemia, dehydration and thrombosis. Pre-Ramadan education and preparation of a fasting patient are essential to reduce severe complications. This review paper summarizes studies to date on oral and injectable medications available for patients with type 2 diabetes during Ramadan fasting, as well as recommendations on management of these patients during Ramadan. Although there is limited data on the use of Metformin, Acarbose and Thiazolidinedione in Ramadan, they appear to be safe. Sulphonylurea, especially Glibenclamide, is associated with higher risk of hypoglycemia during Ramadan fasting, hence may need adjustment in dosing and timing. The incretin group and SGLT2 inhibitor use during Ramadan fasting is associated with low risk of hypoglycemia with no increased adverse events. Insulin regimes need to be individualized for patients who fast during Ramadan.